Inhibition of tau aggregation by a rosamine derivative that blocks tau intermolecular disulfide cross-linking - Haque, Md. Mamunul; Kim, Dohee; Yu, Young Hyun; Lim, Sungsu; Kim, Dong Jin; Chang, Young-Tae; Ha, Hyung-Ho; Kim, Yun Kyung (TAYLOR & FRANCIS LTD, 2014)
Abnormal tau aggregates are presumed to be neurotoxic and are an important therapeutic target for multiple neurodegenerative disorders including Alzheimer's disease. Growing evidence has shown that tau intermolecular disulfide cross-linking is critical in generating tau oligomers that serve as a building block for higher-order aggregates. Here we report that a small molecule inhibitor prevents tau aggregation by blocking the generation of disulfide cross-linked tau oligomers. Among the compounds tested, a rosamine derivative bearing mild thiol reactivity selectively labeled tau and effectively inhibited oligomerization and fibrillization processes in vitro. Our data suggest that controlling tau oxidation status could be a new therapeutic strategy for prevention of abnormal tau aggregation.